Pengaruh Modifikasi Polianilin terhadap Kinerja Elektrokimia Elektroda Reduced Graphene Oxide untuk Superkapasitor - Nina Aprilini; Nur Hayati; Pratiwi Sanggusti; Rahmat Hidayat; Yahdi Bin Rus (Lembaga Pengembangan Kinerja Dosen, 2026)
Supercapacitors have attracted considerable attention as energy storage devices due to their high power density, rapid charge-discharge capability, and long cycle life. However, the relatively low capacitance of reduced graphene oxide (rGO) limits its electrochemical performance when used as a single electrode material. This study aimed to investigate the effect of polyaniline (PANI) deposition on rGO electrodes through an electrochemical deposition method using a 5 mM aniline solution. The rGO electrode was first prepared on a stainless-steel substrate, followed by PANI deposition using cyclic voltammetry within a potential window of −0.4 to +0.4 V at a scan rate of 100 mV s⁻¹ for 10 cycles. The electrochemical performance of the fabricated electrodes was evaluated by cyclic voltammetry and cycling stability tests up to 1000 cycles. The cyclic voltammogram of the rGO/PANI electrode maintained a quasi-rectangular profile, indicating that the electrochemical deposition process produced an active electrode capable of charge storage. The specific capacitance of the rGO/PANI electrode reached 308.87 F g⁻¹, which was higher than that of pristine rGO at 240.88 F g⁻¹. Furthermore, the rGO/PANI electrode retained 67% of its initial capacitance after 1000 cycles, whereas pristine rGO retained only 49%. These results indicate that the incorporation of PANI improved both the specific capacitance and cycling stability of the electrode. The findings demonstrate that electrochemically deposited PANI is a promising approach for enhancing the electrochemical performance of rGO-based supercapacitor electrodes.